A comprehensive report on severe acute respiratory syndrome coronavirus-2 lineages in Puducherry from 2020 to 2023 - Philomenadin, Ferdinamarie Sharmila; Rajendran, Reshma; Ratchagadasse, Vimal R.; Dhodapkar, Rahul (International Journal Of Community Medicine And Public Health, 2025)
This study presents the first comprehensive molecular epidemiology of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in Puducherry, India, from 2020 to 2023, analyzing 1,840 sequences from S gene and whole-genome sequencing. Initial waves saw clade G dominance, followed by delta (clade GK) and Omicron (clade GRA) variants. High mutation density was observed in the spike protein’s N-terminal domain, including key mutations like D614G, E484 variants, N501Y, and P681H. The beta-associated A701V mutation was also detected. Findings align with global trends, showing variant transitions and spike mutations influencing infectivity and immune evasion. This work enhances understanding of regional SARS-CoV-2 evolution and variant dynamics.